Suppository: A Recent Advancement in Rectal Drug Delivery System - Prachi Jain; Dr. Vikrant Wankhade; Dr. Sandeep Atram; Dr. Nishan Bobade; Dr. Shrikant Pande (Asian Journal of Pharmaceutical Research and Development, 2025)
Suppositories are pharmaceutical dosage form that holds a critical function within the realm of drug delivery. This evaluation presents a comprehensive advent to suppositories. This text explores the diverse factors of suppository formulations and therapeutic packages. This overview emphasizes the significance of suppositories as a treasured drug shipping option and the role they play in addressing particular affected person wishes. It also talk the essential additives of suppositories along with bases and lively pharmaceutical components along with the techniques of suppository guidance. The development and method of suppositories require a deep information of various factors which include base choice, drug compatibility, and affected person choices. the selection of base influences the discharge and absorption characteristics of drug, making it is a pivotal concerns in suppository design. Their importance lies not only of their precise mode of administration however also in their ability to provide solutions for precise patient needs, inclusive of instances of nausea, vomiting or problems with oral medication.